Facial Nerve Preservation With Inferior Long-Axis Dissection of Large Vestibular Schwannomas. Issue 1 (January 2023) - Totten, Douglas J.; Connell, Nathan T.; Howser, Lauren A.; Colomb, Elaine; Sandelski, Morgan M.; Rabbani, Cyrus C.; Savage, Jesse J.; Shah, Mitesh V.; Nelson, Rick F.
Abstract : Objective: To describe a tumor resection using the inferior long-axis (ILA) technique for cisternal facial nerve dissection in large vestibular schwannomas (VS). Study Design: Retrospective case series from 2018 to 2021. Setting: Tertiary academic medical center. Patients: Patients who underwent surgical resection with ILA facial nerve dissection of VS (>2.0 cm measured parallel to the petrous ridge) and had at least 3-month follow-up. Interventions: Cisternal facial nerve dissection during retrosigmoid or translabyrinthine approach using standardized ILA technique developed by author R.N. Main Outcome Measures: Immediate postoperative and last follow-up facial nerve function with House-Brackmann scores of I to II defined as "good" facial nerve function and House-Brackmann scores III to VI defined as "poor" function. Extent of resection was also assessed. Results: A total of 48 patients underwent large VS resection with ILA dissection of tumor off of the facial nerve from 2018 to 2021. Mean (standard deviation) tumor size was 3.11 (0.76) cm. Mean (standard deviation) follow-up was 9.2 (9.0) months. Gross-total resection or near-total resection were achieved in 75% (radiographic estimate) to 83% (surgeon estimate) of cases. End-of-case facial nerve stimulation at 0.05 mAmp with a response of at least 240 mV was achieved in 80.4% of patients. Good facial nerve function was observed in 72% immediately postoperatively, 70% 1-month postoperatively, and 82% of patients at last follow-up. Conclusions: The ILA technique is now the method of choice of the senior surgeon (R.N.) when performing microsurgical dissection of the cisternal facial nerve, with which he has achieved high rates of total or near-total resection with excellent facial nerve preservation.